Antioxidant capacity in fruit of Citrus cultivars with marked differences in pulp coloration: Contribution of carotenoids and vitamin C. (April 2021) - Zacarías-García, Jaime; Rey, Florencia; Gil, José-Vicente; Rodrigo, María J; Zacarías, Lorenzo
The purpose of this study was to evaluate the specific contribution of carotenoids and vitamin C to the lipophilic and hydrophilic antioxidant capacity, respectively, of the pulp of citrus fruits using the genetic diversity in pigmentation and in the carotenoid complement. To this end, six citrus varieties were selected: two mandarins, Clemenules ( Citrus clementina ) and Nadorcott ( C. reticulata ); two grapefruits ( C. paradisi ), Marsh and Star Ruby; and two sweet oranges ( C. sinensis ), Valencia late and Valencia Ruby. Total carotenoid content and composition in the pulp of fruits were very different, in relation to their color singularities. Valencia Ruby and Nadorcott had the highest carotenoid content, accumulating the former large amounts of linear carotenes (phytoene, phytofluene, and lycopene) and Nadorcott of β-cryptoxanthin. Orange fruits contained the highest amount of vitamin C while in Nadorcott mandarin it was substantially lower. Analysis of antioxidant capacity, evaluated by 2, 2'-azino-di-(3-ethylbenzthiazoline sulfonate) (ABTS) and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assays, in the pulp of the different fruit varieties indicated a high and positive correlation between vitamin C content and hydrophilic antioxidant capacity. Nevertheless, a weak correlation was observed between carotenoids content and lipophilic antioxidant capacity in the pulp extracts assayed by ABTS. Overall, vitamin C in the pulp of citrus fruit had an important contribution to the hydrophilic antioxidant capacity, whereas that of carotenoids to lipophilic antioxidant capacity was very variable, being the highest that of Valencia Ruby orange, with large concentrations of lycopene and phytoene, followed by Nadorcott mandarin, with high β-cryptoxanthin content.